The Effectiveness of Using Personal Photograph as Media in Teaching Writing of Descriptive Text at SMK Sore Tulungagung: A quantitative of research study - Fase Meida; Erna Dwinata (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2022)
This research aimed to determine the effectiveness of students' writing descriptive text taught using Personal Photograph at tenth-grade students of SMK “Sore”. In this research, the researcher used pre-experimental with a one- group pretest-posttest design. The instrument of this research was a test. The researcher gave a pre-test to the student, and then treatment about writing using Personal Photograph. After that, the researcher gives the student post-test. The population was all students of grade tenth SMK “Sore” Tulungagung with 800 students. The researcher used purposive sampling was taken X TITL 1 as the sample with total was 27 students. After getting enough data, the researcher calculated the data using the t-test. Based on the computation, the mean score of the pre-test is 5.70 and the mean of the post- test 8.41. The t-value is -9.782 consulted to the t-table at the -2.056 significance level to see whether the hypothesis is accepted or rejected. It means that t-value is lower than t-table. So, it can be stated that the hypothesis is accepted. Based on the result analysis, the researcher then concludes that using Personal Photograph effectively improved the students’ writing descriptive text at the tenth-grade students of SMK “Sore” Tulungagung.